Accidental oculofacial vaccinia - Dilmen, Uğur; Kanra, Güler (The Turkish Journal of Pediatrics, 1982)
A case of accidental oculofacial vaccinia and the course of treatment are presented. Although smallpox vaccination is no longer recommended, attention should be drawn to the complications and to the appearance of the lesions, which may aid the physician in making a diagnosis.
Keywords: keratitis; oculofacial vaccinia complication; orbital cellulitis; vaccinia